2019
DOI: 10.1027/1015-5759/a000426
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Version of the HIV-Related Attitudes Scale (HIV-AS) for Adolescents

Abstract: Abstract. The HIV-related Attitudes Scale (HIV-AS) is a brief, valid, and reliable instrument, widely used in Spain. Because of the high risk of HIV in adolescents in Portugal and the scarcity of multidimensional measures to assess attitudes toward HIV-related aspects, reliable and valid instruments are essential for understanding sexual risk behaviors in this population. The aim of this study was to adapt and validate the Spanish version of the HIV-AS into Portuguese. Factor structure, internal consistency, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the second case, results are in line with a study by Uribe, Orcasita, and Vélez [ 40 ] with Colombian population, who found a relationship between susceptibility to the consequences of diseases and attitudes toward health protection behaviors, such as using condoms. Moreover, moderate positive correlations were found among all the HIV-AS subscales and most of the factors in the scale of knowledge about HIV and other STDs, which suggests that more knowledge results in better attitudes toward HIV, as has been found by theorical authors as Ajzen [ 5 ] and authors working with the Portuguese version of the scale [ 19 ] and also by authors studying Colombian populations [ 41 , 42 ]. It is important to highlight that, given that the constructs are different, all correlations were low or moderate, which stresses the differences between constructs despite their being related.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the second case, results are in line with a study by Uribe, Orcasita, and Vélez [ 40 ] with Colombian population, who found a relationship between susceptibility to the consequences of diseases and attitudes toward health protection behaviors, such as using condoms. Moreover, moderate positive correlations were found among all the HIV-AS subscales and most of the factors in the scale of knowledge about HIV and other STDs, which suggests that more knowledge results in better attitudes toward HIV, as has been found by theorical authors as Ajzen [ 5 ] and authors working with the Portuguese version of the scale [ 19 ] and also by authors studying Colombian populations [ 41 , 42 ]. It is important to highlight that, given that the constructs are different, all correlations were low or moderate, which stresses the differences between constructs despite their being related.…”
Section: Discussionmentioning
confidence: 57%
“…A qualitative analysis showed that the items were adequately constructed: Aiken’s V 95% limit was higher than 0.50 in all cases. The exploratory factor analysis revealed a four-factor structure that reflects the original version and the Portuguese version [ 17 ]; all of the factors in our version explain 70% of total variance, whereas in the original version factors explain 64,63% of total variance [ 19 ]. In general, the indicators of the psychometric properties of the items were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation